CONTRIBUTION OF COLORS TO INDIAN PAINTING (WITH SPECIAL REFERENCE TO ABDURRAHMAN CHUGHTAI): भारतीय चित्रकला में रंगों का योगदान (अब्दुर्रहमान चुगताई के विषेष संदर्भ में) - Irfan, Nazima (International Journal of Research -GRANTHAALAYAH, 2014)
Varna has an important place in human life. Each item has some color. Human attraction to colors has never decreased. That is why from the initial human to the modern human, Varna has taken support in the development of beauty. From the color arrangement of the room to the color scheme of the flowering plants in the garden gardens, the artist has made his intervention as colors have their own effect which has the power to evoke the mental feelings of human. Varna is universal and color is given the most importance in painting. Feelings of the mind are associated in various forms of colors like orange in the color of spring, blue of cloud, yellow of lamp, green of Sri, black of Malakosh and white of Bhairava which form the basis of paintings. The artist had become conscious of color since Ajanta. The colors that could not emerge so much in Ajanta, burst into Rajasthani and mountain pens with their full-blown chatter and became expressive like the expressionism and fascism of Europe. This tradition continued to develop from the Ajanta era to the 16th century through Jain art. मानव जीवन में वर्ण का महत्वपूर्ण स्थान है। प्रत्येक वस्तु कोई न कोई रंग लिये हुए है। रंगों के प्रति मानव का आकर्षण कभी घटा नही है। इसीलिये आदि मानव से लेकर आधुनिक मानव तक ने सौन्दर्य के विकास में वर्ण का सहारा लिया है। कमरे की रंग व्यवस्था से लेकर बाग बगीचों में फूल पौधों की रंगयोजना तक में कलाकार ने अपना हस्तक्षेप किया है क्योंकि रंगों का अपना एक प्रभाव होता है जो मानव की मानसिक भावनाओं को उद्वेलित करने की शक्ति रखता है। वर्ण सार्वभौमिक है तथा चित्रकला में सबसे अधिक महत्व रंग को दिया जाता है। रंगों के विविध रुपों में मन की भावनायें जुड़ी हैं जैसे बसन्त का रंग नारंगी, मेघ का नीला, दीपक का पील, श्री का हरा, मालाकोश का काला और भैरव का सफेद जो चित्रों के आधार बने। अजन्ता काल से ही कलाकार रंग के प्रति सजग हो गया था। रंग जो अजन्ता में इतना उभार नहीं पा सके थे वे राजस्थानी व पहाड़ी कलम में अपनी पूर्ण चटख मटक के साथ फूट पड़ते हैं तथा यूरोप के अभिव्यंजनावाद व फावीवाद की तरह अभिव्यक्तिपरक हो गये। अजन्ता युग से लेकर जैन कला से होती हुई 16वीं शताब्दी तक इस परम्परा का विकास होता रहा।